Catálogo y registro del repertorio musical patrimonial que reposa en la Biblioteca del Conservatorio de Música “Salvador Bustamante Celi” de Loja a través del Sistema de Información del Patrimonio Cultural del Ecuador (SIPCE) - Flores Pérez, Karen Sophia (2023)
The repertoire produced in the city of Loja by local composers or from other latitudes who developed artistic activity in this city is stored in repositories that are generally rarely consulted due to the ordering problems they present. In this sense, the preservation of the sound heritage of the city of Loja has become one of the most important tasks to be carried out. Therefore, in this research a process of ordering, classification, registration and cataloging of the patrimonial musical repertoire protected in the Library of the Conservatory of Music "Salvador Bustamante Celi" has been proposed. The transactional non-experimental methodological design, the qualitative approach, and the use of the historical, analytical - synthetic method and descriptive cataloging affected the understanding and interpretation of the reality of the musical documents that are part of the sound heritage. The result of this investigation is the Catalog of the patrimonial musical repertoire that rests in the Library of the Conservatory of Music "Salvador Bustamante Celi", which was carried out within the framework of the Ecuadorian Pianistic Repertoire Project. Loja Chapter. Keywords: Sound heritage, cataloging, music in Loja, SIPCE, Ecuadorian heritage music.